PERAN PENTING EKONOMI ISLAM DALAM PEMBANGUNAN EKONOMI NASIONAL: KAJIAN AUTOETNOGRAFI DALAM BIDANG EKONOMI - Dwi Novaria (Jurnal Manajemen dan Penelitian Akuntansi (JUMPA), 2020)
As a universal, integral and comprehensive system of life Islam has established a complete order for human life. As a way of life, Islam arranges everything related to life, from the simplest to the most complicated matters. The method in this research is descriptive qualitative. The type of qualitative research used is autoetnography. This research was also conducted with a theoretical approach to Islamic economics. In obtaining data, researchers used observation and documentation techniques.Both in the aspects of politics, economics, education, art, social, culture, etc. Islam is a perfect religion, which regulates matters relating to the economy. If a country's economy (national economy) applies the basic Al-Quran and Hadith as the basis for its application, surely a national economy will run well and be directed according to the rules. But the fact is that not all Muslim countries in the world apply this basis. Furthermore, this article explains how Islamic Economy contributes to national economic development, especially Indonesia as a country with the largest Muslim base in Asia.